Conversion of nitroalkanes into carboxylic acids via iodide catalysis in water. Issue 5 (23rd November 2015) - Marcé, Patricia; Lynch, James; Blacker, A. John; Williams, Jonathan M. J.
Abstract : Carboxylic acids are prepared in good yields from nitroalkanes catalysed by a combination of a Lewis acid with iodide. Abstract : We report a new method for the conversion of nitroalkanes into carboxylic acids that achieves this transformation under very mild conditions. Catalytic amounts of iodide in combination with a simple zinc catalyst are needed to give good conversions into the corresponding carboxylic acids.